Cross-sectional comparison of office and ambulatory pulse wave velocity by two methods, and their changes after lifestyle or medical interventions in hypertension. Issue 3 (26th March 2022) - Batta, Dóra; Körösi, Beáta; Gyöngyösi, Helga; Nemcsik-Bencze, Zsófia; László, Andrea; Tislér, András; Cseprekál, Orsolya; Nemcsik, János
Abstract : Supplemental Digital Content is available in the text Abstract : Objective: Pulse wave velocity (PWV), the most accepted biomarker of arterial stiffening can be measured by different methods and in the past decade, its 24 h monitoring has also become available. The aim of our study was to compare office and ambulatory PWVs and in a proportion of patients to compare the changes of PWVs after the initiation of lifestyle modifications or antihypertensive medication. Methods: Office carotid–femoral PWV was measured with the tonometric PulsePen device (PP PWV), first hour and 24 h ambulatory oscillometric PWVs were evaluated with Mobil-O-Graph (MOB first hour PWV and MOB 24 h PWV, respectively). In new hypertensive patients, the measurements were repeated 3 months after the initiation of antihypertensive medication. In white-coat hypertensive patients after lifestyle modifications the measurements were repeated at 12 months. Results: One hundred and five participants were involved with 22 new hypertensive and 22 white-coat hypertensive (WhHT) patients. PP PWV [8.7 (7.3–9.9) m/s] differed from MOB first hour PWV [7.3 (6.5–8.8) m/s] and MOB 24 h PWV [7.4 (6.4–8.8) m/s] as well ( P  < 0.05). PP PWV significantly decreased both in hypertensive [by 0.9 (0.4–1.5) m/s, P  < 0.05] and WhHT patients [by 0.3 (−0.1 to 1) m/s, P  < 0.05]. MOB first hour PWV did not change neither in hypertensive patients, nor in WhHT patients. MOB 24 h PWV decreased only in hypertensive patients [by 0.2 (0–0.6) m/s], which was less pronounced compared with PP PWV ( P  < 0.05). Conclusion: The significant differences observed both in the cross-sectional and in the prospective parts of our study suggests that the two methods are not interchangeable.